2014
DOI: 10.7150/ijms.8358
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Co-Expression of miRNA-5p and -3p Species and Cross-Targeting in Induced Pluripotent Stem Cells

Abstract: Background: A miRNA precursor generally gives rise to one major miRNA species derived from the 5' arm, and are called miRNA-5p. However, more recent studies have shown co-expression of miRNA-5p and -3p, albeit in different concentrations, in cancer cells targeting different sets of transcripts. Co-expression and regulation of the -5p and -3p miRNA species in stem cells, particularly in the reprogramming process, have not been studied.Methods: In this work, we investigated co-expression and regulation of miRNA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 54 publications
2
37
0
Order By: Relevance
“…Both the -5p and -3p arms of miR-21 were downregulated to a similar extent, which suggests regulation at the level of initial transcription of the miR-21 precursor. In fact, this same pattern of regulation was observed for other seven miRNAs (mmu-miR-29c, mmu-miR-296, mmu-miR-130b, mmu-miR-17, mmu-miR-434, mmu-miR-181c, mmu-miR-132), which further confirms the validity of our analysis and suggests miRNA regulation at the gene expression level [48]. Although it is found at much lower levels, it has been suggested that the 3p arm can also possess regulatory activity [49].…”
Section: Discussionsupporting
confidence: 87%
“…Both the -5p and -3p arms of miR-21 were downregulated to a similar extent, which suggests regulation at the level of initial transcription of the miR-21 precursor. In fact, this same pattern of regulation was observed for other seven miRNAs (mmu-miR-29c, mmu-miR-296, mmu-miR-130b, mmu-miR-17, mmu-miR-434, mmu-miR-181c, mmu-miR-132), which further confirms the validity of our analysis and suggests miRNA regulation at the gene expression level [48]. Although it is found at much lower levels, it has been suggested that the 3p arm can also possess regulatory activity [49].…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, mir-1307 was differentially expressed under MYCN knockdown, but showed reversed regulation in the 5p/3p species. Although the reverse direction of 5p/3p coexpression has been reported in several studies [56, 57], the mechanism and biological significance of preferred arm selection remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Despite originating from the same transcribed pri-miRNA, it is not unusual for 3p and 5p strands from the same pri-miRNA to be expressed differently in mature form in response to different stimuli. By nature of being complimentary to one another, 3p and 5p strands can have very different targets, eliciting effects with negative or positive feedback on the degradation of these strands (5052). Additionally, HIF-1α silencing restored miR-155-5p levels, indicating that in mast cells, HIF-1α negatively regulates miR-155-5p expression.…”
Section: Discussionmentioning
confidence: 99%